(untitled) (Biodiversitas Journal of Biological Diversity, 2007)
The objective of this research was to increase the viability of the paddy straw mushroom spawn by adding natural stone on the mediaâ€™s composition for the paddy straw mushroom spawn. Mycelium of the paddy straw mushroom was take from the pure development of the paddy straw mushroom which was planted on the various treatment for media e.i. 100% cotton media and rice bran + 0% zeolite (A), 75% cotton media and rice bran + 25% zeolite (B), 50% cotton media and rice bran + 50% zeolite (C), 25% cotton and rice bran + 75% zeolite (D), 0% cotton media and rice bran + 100% rice bran (E). Each treatment was observed for the length of mycelium, the concentration of reduced sugar, total carbon and water content, spawn media weight, pH and temperature. Results demonstrated that there is a positive effect of zeolite added to the paddy straw mushroom media. The zeolite able to adsorbed nutrient through its pores, so the mycelium of the paddy straw mushroom able to use the nutrient gradually and equally appropriate with its growth. Therefore the viability of the paddy straw mushroom is increase. Result showed that the B is the best viability in the Potetos Dectrose Agar (PDA) media, that has viability power up to 50 days after inoculation and the temperature are 29,6 0C, then followed by treatment C, D, A and E, each has viability power up to 42; 38; 34; 22 days after inoculation and the maximum length of each mycelium are 17.5; 9.2; 0.9; 0.5 cm, but in the treatment D being contaminated by Aspergillus sp. Â© 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: Zeolite, viability, paddy straw mushroom spawn.